A dielectric resonator based line stripe miniaturized ultra‐wideband antenna for fifth‐generation applications. (12th January 2021) - Mahmud, Md. Zulfiker; Samsuzzaman, Md; Paul, Liton Chandra; Islam, Md Rashedul; Althuwayb, Ayman A.; Islam, Mohammad Tariqul
Summary: This work presents an original dielectric resonator based line stripe miniature ultra‐wideband (UWB) antenna for 5G applications. The length, width, and height of the designed antenna are 23, 15, and 1.605 mm, respectively. The projected antenna prototype is composed of a simple line structure‐based modified scattered patch and a rectangular ground plane consisting of a saw tooth orientation in the upper end. A number of rectangular resonators are placed on both sides of the patch and ground to optimize the desired results. This technique ensures the lower operating band and made a significant improvement of efficiency without compromising the antenna size. The proposed design obtained the range of frequency bandwidth from 3.55 to 4.2 GHz under the −10‐dB scale, which covers the lower fifth‐generation (5G) communication band offered by Federal Communications Commission (FCC). The moderate gain and more than 80% radiation efficiency at a resonant point with strong fidelity factor confirms the usability and lower signal distortion of the antenna. The design offers an omnidirectional radiation pattern with 90° elevated directivity for cross polarization. This proposed design is compact in size and can be integrated into limited space around microwave circuitry with low manufacturing cost. The performance parameters like operating bandwidth, antenna size, and area of application, dielectric constant, fractional bandwidth, and omnidirectional radiation pattern were proposed as a suitable candidate for 5G application. Abstract : The essential design considerations and unprecedented challenges of hardware for future fifth‐generation (5G) cellular devices are presented with the practical deployment of methodology. A line stripe based miniaturized ultra‐wideband (UWB) antenna is proposed for 5G applications. The obtained results comply with the 5G application covering the priority one frequency range (3.3 to 4.2 GHz) allocated by FCC.